Chi-square test on Islamic Economic Research - Siti Nur Indah Rofiqoh; Ririn Triratnasari; Nelly Rahmatillah; Fatin Fadhilah Hasib; Alimin Alimin (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2023)
In Islamic economic research, we may collect categorical variable data. Using statistical analysis, chi-square test can be an alternative to evaluate those data. Furthermore, the analysis of chi-square test can be aimed at evaluating the differences between study groups according to the assign degree of error. This article also explains the purpose of chi-square test, the Karl Person chi-square hypothesis, what type of data can use in chi-square test, the assumptions of chi-square analysis and also the rule to analyze categorical variables data in sharia economics research.